Child Characteristics, Parent Education and Depressive Symptoms, and Marital Conflict Predicting Trajectories of Parenting Behavior from Childhood Through Early Adolescence in Taiwan. Issue 3 (23rd September 2016) - Hsieh, Yi‐Ping; Dopkins Stright, Anne; Yen, Lee‐Lan
Abstract : The study examined how child and parent characteristics, and contextual sources of stress, such as marital conflict predict initial status and trajectories of parent involvement, support, and harsh control, over a 4‐year period in families in Taiwan ( n  =   4, 754). Based on Belsky's (1984) ecological model of parenting, three domains predicting parenting were tested, child characteristics (age cohort and gender), father and mother characteristics (education and depressive symptoms), and contextual sources of stress (marital conflict). The study followed two cohorts of children; the younger cohort was followed from first to fourth grade and the older cohort from fourth to seventh grade. Initially, fourth graders reported more parental involvement, support, and harsh control than first graders. However, involvement, support, and harsh control decreased across the 4 years for the older cohort as they transitioned to early adolescence. In the first year, girls reported more parental involvement and support and less harsh control than boys. Across the 4 years, involvement and support increased, and harsh control decreased for boys; whereas involvement stayed the same, support slightly decreased, and harsh control slightly increased for girls. Children whose parents were more educated reported more parent involvement, support, and harsh control in the first year. Children whose fathers were chronically depressed and whose parents were experiencing marital conflict reported decreasing parent involvement and support over the years.